KELIMPAHAN BAKTERI RIZOSFER PADA SISTEM PHT-BIOINTENSIF SERTA KEMAMPUAN ANTAGONISMENYA TERHADAP Sclerotium rolfsii PADA KEDELAI - Abdjad Asih Nawangsih; Tita Widjayanti .; Yana Anisa . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
Abundance of rhizospheric bacteria on the IPM-Biointensive system and their antagonistic activities toward Sclerotium rolfsii on soybean. Abundance of beneficial microorganisms in the soil is one of the active soil indicators the success of integrated pests management (IPM) system. Some beneficial groups of microorganisms can be used as biocontrol agents. This experiment was conducted to evaluate the effects of IPM-Biointensive by integrated application of resistant varieties, rice-straw mulch, and biocontrol agents on the abundance of rizospheric bacteria of soybean, also to evaluate the suppressiveness of the bacteria to the mycelial growth of S. rolfsii in vitro. Abundance of the bacteria was determined by isolation using serial dilution and plate-count techniques. Suppression to the fungus was evaluated using dual culture technique. Heat tolerant bacteria had the highest abundance (ranged 1011-1012 cfu/g soil), followed by non-fluorescence bacteria (1011 cfu/g soil), chitinolytic bacteria (106-109 cfu/g soil), and fluorescence bacteria with population range was 103-108 cfu/g soil. Gepak kuning variety grown with application of rice-straw mulch and PGPR (V2M1P1) caused the highest abundance of rizosphere bacteria. One of the heat tolerant bacteria, i.e. TP32, caused the highest suppression to the mycelial growth of S. rolfsii in vitro. Based on the morphology, physiology, and biochemical properties, the isolate was identified as Bacillus sp.